Experimental investigation of phase change of medium/high temperature paraffin wax embedded in 3D periodic structure. (August 2020) - Righetti, Giulia; Doretti, Luca; Zilio, Claudio; Longo, Giovanni A.; Mancin, Simone
Highlights: A 70 °C paraffin wax was used as PCM in a latent heat storage. Three 3D aluminum periodic structures were realized via additive manufacturing. The 3D periodic structures were experimentally tested to enhance the heat transfer. The temperature field was analyzed during melting and solidification. A model to estimate the maximum junction temperature was proposed. Abstract: In the scientific and industrial community, the interest on Latent Thermal Energy Storages (LTESs) is continuously increasing. These components can be easily coupled with intermittent renewable energy sources and with heat sources that undergo to cycling operations. Phase Change Materials (PCMs) are considered convenient and reliable media to be used in LTES. Nevertheless, their low thermal conductivity remains the greatest hindrance that still limits their technological application. The present work aims at increasing the effective thermal conductivity of a paraffin wax, the RT70, having a phase change temperature of 70 °C. This paper proposes the addition of a 3D metallic periodic structure to the PCM. To optimize the geometry, three different structures with 10, 20, and 40 mm base sizes were designed and manufactured via additive manufacturing. Experimental tests were run during the melting and the solidification of RT70 at three different heat fluxes (10, 20, and 30 W). The addition of the 3D aluminum structure in the PCM remarkably improved the heat transfer performance as compared to the reference empty box. The best geometry was identified, and a correlation was proposed to evaluate the charging time.